Perceived parental control and disclosure of adolescents with disciplinary problems - Arshat, Zarinah; Ang, Chun Ee (Canadian Center of Science and Education, 2017)
Disciplinary violation are commonly found among school-going adolescents. The current study examined the relationship between parental control and disclosure among adolescents with disciplinary problems. A total of 354 adolescents were recruited using multistage cluster random sampling technique in Selangor. Results from the correlational analysis revealed that the higher the paternal and maternal control on adolescents, the higher the adolescents' disclosure to their father and mother. This suggests that prevention strategies focusing on parental control in relation to disclosure is applicable to adolescents with disciplinary problems.